Innovation of Learning Tools Based on the Caplaire Model to Improve Scientific Literacy Skills - Ananda, Lala Jelita; Simanihuruk, Lidia; Zati, Vidya Dwi Amalia (Jurnal Paedagogy, 2024)
This research aims to produce a Student Worksheet based on the Caplaire Model to improve scientific literacy skills for Elementary School Teacher Education students that is valid, practical, and effective. This research is development research using the ADDIE model which includes 5 stages, namely: Analyze, Design, Development, Implementation, and Evaluation. The research instruments used in product development consist of material expert validation and design expert validation instruments, student response questionnaire instruments to products, and product effectiveness test question instruments. The data analysis technique used in this research was quantitative and qualitative descriptive data analysis. The research results obtained were: 1) The results of the material expert validation test using the material expert validation instrument obtained a score of 84% with a very feasible category; 2) The results of the design expert validation test using the design expert validation instrument obtained a score of 86% with a very feasible category; 3) The results of the practicality test using the lecturer response questionnaire instrument obtained a score of 85% in the very practical category; 4) The results of the effectiveness test using question instruments for students showed an increase in scores in the initial test and final test, in the initial test the average score was 60.8 and in the final test the average score was 82.8. So, through this development research, student worksheets based on the Caplaire Model were obtained that were valid, practical, and effective.